1981
DOI: 10.1136/bmj.282.6270.1111
|View full text |Cite
|
Sign up to set email alerts
|

Five year follow-up of effects of treatment of mild and moderate hypertension.

Abstract: HALFORD-MAW, R EVANS AbstractA five-year follow-up study of the effects of treating patients with both mild and moderate hypertension was performed. The patients were identified during a hospital-based community survey of hypertension. A total of 961 patients were divided into four groups. The first group, the controls, were age-and sex-matched normotensive subjects selected sequentiallyfrom the same survey. The second group were patients defined as wellcontrolled hypertensives; the third group were patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
2
1

Year Published

1983
1983
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 6 publications
2
14
2
1
Order By: Relevance
“…This difference may have been due to the smaller number of BP measurements in our study (3 during 1 year) compared with the NHANES-III survey (6 during 2 visits), which would tend to overestimate the prevalence of hypertension. 14a This study not only confirms the strong association between achieved BP and risk of stroke among treated hypertensive patients 5,[15][16][17] but also provides separate estimates for ischemic and hemorrhagic stroke and the proportion of these strokes that may have been attributable to inadequate control of BP. SBP was more strongly associated with the risk of hemorrhagic stroke than DBP, whereas DBP and SBP were similarly associated with the risk of ischemic stroke.…”
Section: Discussionsupporting
confidence: 62%
“…This difference may have been due to the smaller number of BP measurements in our study (3 during 1 year) compared with the NHANES-III survey (6 during 2 visits), which would tend to overestimate the prevalence of hypertension. 14a This study not only confirms the strong association between achieved BP and risk of stroke among treated hypertensive patients 5,[15][16][17] but also provides separate estimates for ischemic and hemorrhagic stroke and the proportion of these strokes that may have been attributable to inadequate control of BP. SBP was more strongly associated with the risk of hemorrhagic stroke than DBP, whereas DBP and SBP were similarly associated with the risk of ischemic stroke.…”
Section: Discussionsupporting
confidence: 62%
“…14 Few studies did not find any effect of hypertension treatment on CVD mortality. 11,13,15 However, their follow-up times were rather short, 7 years 11 and 5 years, 13 respectively, and it may be argued that exposure time was not sufficient to show any beneficial effect of antihypertensive therapy. It is also possible that changes in hypertension care have influenced outcomes obtained during the long-term follow-up.…”
Section: Control Of Hypertension Nc Barengo Et Almentioning
confidence: 99%
“…[6][7][8][9] Controversial results have been published regarding health outcomes in normotensive people with health outcomes in treated and untreated hypertensive patients. [10][11][12][13][14][15] Furthermore studies including women are rare. 10,12,15 The aim of this study was to investigate whether there are differences in CVD and all-cause mortality among hypertensive men and women by awareness, treatment and the BP control status at baseline.…”
Section: Introductionmentioning
confidence: 99%
“…3 Hypertension also results in an increased frequency of ischemic and hemorrhagic stroke. 4 A large body of evidence exists based on case series, 5 population studies, 6,7 and clinical trials 8 demonstrating that control of hypertension reduces risk of initial stroke. It has also been demonstrated that treatment of isolated systolic hypertension in the elderly will reduce risk of stroke.…”
mentioning
confidence: 99%